The Cultural Industry: An Embryonic State in the Face of Associative Motivation - Malika AIT NASSER (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: The study focuses on research on the associative actor mobilized around the heritage issue. Coming from different associations, the speakers in the webinar that is the subject of the production of this article have multiplied the angles of analysis to explore, understand and identify the many variations of heritage. Their concern for socioeconomic development where heritage is at the center of economic activities highlights their understanding of the cultural industry. Methodology: The qualitative content and thematic analysis of the comments collected from the associative actors participating in this webinar aims to better understand the aspects of the intervention of the association actor in a cultural industry project. Heritage, this time, is literally reborn thanks to the efforts of associations, whose role is no longer passive; their experiences of heritage animation are often practiced on a small scale. Findings: In fact, the results show that knowledge of the forms, qualities, and importance of heritage preservation, as well as its market value, are currently attracting the attention of the cultural industry. Implications/Novel Contribution: The study highlights the critical role of associative actors in revitalizing heritage through grassroots cultural initiatives. Understanding heritage as an economic resource opens new pathways for sustainable cultural industry development. The findings support integrating community-based heritage animation into broader cultural policy frameworks.